The Ethics and Economics of Agrifood Competition - James, Jr., Harvey S. (The International Library of Environmental, Agricultural and Food Ethics, 2013)
This edited volume presents ethical and economic analyses of agrifood competition. By systematically examining fairness and openness in agricultural markets, it seeks to answer the question of whether there is adequate competition in the agrifood industry and whether the system is fair to all participants. It outlines ethical and economic principles important for understanding agrifood competition, presents arguments for and against consolidation, globalization and the integration of agrifood industries, and looks at the implications of globalization on the nature of competition in specific agricultural contexts.